Encoding definiteness on pronominal objects in Mordvinic - Mariann Bernhardt (Finnisch-Ugrische Forschungen, 2022)
This article examines the morphosyntax of pronouns in object function and reveals the syntactic and morphological differences between nominal and pronominal objects in Mordvinic. The variation in case marking and declension type of nominal objects is affected by definiteness. Indefinite objects are in the basic declension nominative, whereas definite ones are in the definite or possessive declension genitive. Furthermore, definite objects may be indexed on the verb. In this paper, I analyze the morphosyntax of pronouns, in order to reveal the regularities between semantics and morphological marking and to provide a better understanding of definiteness. For this purpose, the finite forms of perception verbs were collected from the MokshEr corpus, which contains written texts in the literary languages, and native speakers were consulted on the results. Perception verbs were chosen for this study because they agree with the object in person and number more frequently than other semantic classes of verbs, thus providing good material for examining the correlation of definiteness with verbal conjugation. The paper shows how definiteness is displayed within the morphosyntax of pronouns and uncovers how verbal conjugation correlates with different pronominal objects.